Tectono-Thermal Evolution and its Significance of Hydrocarbon Exploration in the Fuyang Sag, Southern North China Basin: A Case Study of Well WFD-1 - Gao, Peng; Li, Zhao; Miao, Miao; Li, Shizhen; Zhang, Hongda (Frontiers in Earth Science, 2022)
The study of tectono-thermal evolution of sedimentary basin reveals both geothermal field characteristics and hydrocarbon generation and expulsion in the basin. However, there are only few studies on the tectono-thermal evolution of the Fuyang Sag. This makes the hydrocarbon exploration in the study area is restricted and unable to be effectively supported. Based on the geophysical exploration and drilling results， the tectono-thermal evolution of the Fuyang Sag has been studied for the first time in this paper. Using the organic geochemical data of the source rocks, the influence of tectono-thermal evolution on hydrocarbon exploration in the Fuyang Sag was discussed. The burial history of the Fuyang Sag since the late Paleozoic fall into four stages: stable sedimentation, rapid subsidence and deposition, long-term continuous uplift and denudation, sedimentation. The heat flow evolution history of the Fuyang Sag since the late Paleozoic is characterized by ascending first and descending afterwards. The main source rocks in the sag increased rapidly during the Permian, and was gradually finalized in the Yanshanian period. The Fuyang Sag was reformed after the early hydrocarbon generation. The main source rocks with deeper burial depth, weaker uplift and denudation reformation have greater potential for hydrocarbon exploration in the sag. The results of this study provide not only a scientific basis and important guidance for hydrocarbon exploration in the Fuyang Sag, and but also effective geothermal constraints for further geodynamics research in the Southern North China Basin.